VARIETIES AND LINES OF BREAD WHEAT WITH VALUABLE AGRONOMIC TRAITS (Eurasian Journal of Academic Research, 2026)
The article highlights the analysis of scientific research results conducted in 2025 on productive, high-yielding new varietal samples of rainfed bread wheat with valuable traits and properties in the control variety field.